2017
DOI: 10.1111/dom.12845
|View full text |Cite
|
Sign up to set email alerts
|

Robust GLP‐1 secretion by basic L‐amino acids does not require the GPRC6A receptor

Abstract: The G protein-coupled receptor GPRC6A (GPCR, Class C, group 6, subtype A) has been proposed to be a sensor for basic L-amino acids that are hypothesized to translate ingestive behaviour to endocrine information. However, the contribution of the GPRC6A receptor to L-amino acid-induced glucagon-like peptide 1 (GLP-1) secretion is unclear. Therefore, to discover whether the GPRC6A receptor is indispensible for amino acid-induced secretion of GLP-1, we treated, with oral gavage, GPRC6A knock-out (KO) and wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 25 publications
(34 reference statements)
1
24
0
Order By: Relevance
“…Because of a lack of potent and selective ligands, these suggested functions have mainly been investigated by phenotyping of knock-out mice where the gene function has been destroyed by deletion of exon 6 (Bräuner-Osborne group (17)), exon 2 (Quarles (18) and Karsenty (14) groups), or the full gene (Murphy (19) and Bräuner-Osborne groups (20)). Under normal physiological conditions, these mouse strains have shown very different phenotypes.…”
mentioning
confidence: 99%
“…Because of a lack of potent and selective ligands, these suggested functions have mainly been investigated by phenotyping of knock-out mice where the gene function has been destroyed by deletion of exon 6 (Bräuner-Osborne group (17)), exon 2 (Quarles (18) and Karsenty (14) groups), or the full gene (Murphy (19) and Bräuner-Osborne groups (20)). Under normal physiological conditions, these mouse strains have shown very different phenotypes.…”
mentioning
confidence: 99%
“…To test whether this translates to the in vivo state, we have administered L‐ornithine and L‐arginine orally to the full locus and exon VI GPRC6A KO mouse models. We observed robust GLP‐1 release, but while the GLP‐1 secretion was attenuated at later time‐points, there were no overall differences between KOs and WTs, demonstrating that functional GPRC6A is not required for robust secretion of GLP‐1 in vivo by basic L‐amino acids . This suggests that other receptors or mechanisms than GPRC6A are mediating at least some of the effects of L‐arginine and L‐ornithine in vivo.…”
Section: Suggested Physiological Functions Of Gprc6amentioning
confidence: 73%
“…The most recently obtained data using the full locus GPRC6A KO model have supported the lack of abnormalities of the exon VI KO model with respect to bones and metabolism and demonstrated that GPRC6A is not required for robust L‐amino acid‐induced GLP‐1 release in vivo . Other studies indicate a role of GPRC6A in male reproduction, prostate cancer and inflammation, and will be important to validate in other groups/mouse models before firm conclusions can be drawn.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…25 Accumulating evidence has indicated that amino acids are potent stimulators of gut hormone secretion. 26,27 Less understood is the mechanism by which amino acids exert this effect. Among 20 proteogenic amino acids, although both Asp and Glu belong to acidic amino acids, they show different patterns of CCK secretion in pig duodenum.…”
Section: Discussionmentioning
confidence: 99%